Designing a talent management model for the General Directorate of Sports and Youth of Fars Province with a data theory approach - Motlagh, Sayyed Abbas Hosseini; Dehbidi, Vahid Rafiee; Hosseini, Seyed Ehsan Amir (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to identify and develop a talent management model of the General Directorate of Sports and Youth of Fars Province. The research method is qualitative and based on data theory with a systematic approach. The statistical population of this study included experts, professors and researchers in the field of sports management, managers, heads of sports delegations, staff and employees of sports and youth departments in Fars province. Using purposive sampling, 14 semi-structured individual interviews were conducted. Data analysis was performed using the systematic method of Strauss and Corbin, including three-step open, axial and selective coding, which resulted in a total of eighty initial codes; Then, similar codes were reduced to twenty- two sub-categories, and finally, based on the secondary open codes, seven main categories including human factors, organizational factors, organizational strategy and conditions and facilities, human resource management, organizational performance, and employee performance were identified. According to the results of the study, it can be said that managers can prevent talent migration and waste of costs by focusing on the talent management process and using proper human resource management strategies, and improve employee performance and increase organizational productivity and promote sports in Fars province.